The Diagnosis, Treatment and Follow-up of Extracranial Carotid Stenosis - Hans‐Henning Eckstein; A. Kühnl; Arnd Dörfler; I. Kopp; Holger Lawall; Peter A. Ringleb (2013)
Extracranial atherosclerotic lesions of the carotid bifurcation cause 10% to 20% of all cases of cerebral ischemia. Until now, there have been no comprehensive evidence- and consensus-based recommendations for the management of patients with extracranial carotid stenosis in Germany and Austria.